Role of general practitioners in transforming surgical care in rural Nepal - a descriptive study from Eastern Nepal - Dangal, Binod; Pathak, Mandeep; Gauchan, Bikash; Khadka, Man Bahadur; Ng, Jessica (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Nepal is a low-to-middle-income country (LMIC) with a predominantly rural population. Almost 10-20% of patients presenting to hospital require surgical care. The availability of skilled human resources in managing surgical care in rural areas of Nepal has to expand to meet this need. The objective of this study is to describe and demonstrate how General Practitioners (GPs) can be upskilled to provide surgical care in rural district hospitals in Nepal. Method: It is a retrospective review of all surgical procedures performed by GPs from 1st February 2016 to 31st January 2021 at Charikot hospital. Data was collected from a prospectively maintained Electronic Health Record (EHR) system (Bahmini). Details of data collected included name of the procedure and its respective specialty. GP Task shifting and targeted surgical training programs for common orthopedic procedures and pediatric herniotomy were described in detail. Result: A wide range of surgical procedures were performed by GPs over 5 years. This included interventions for obstetric emergencies, trauma and orthopedics, gynecological issues, general surgery of adult and childhood. A total of 2037 surgeries were performed by GPs including: Cesarean section 25%, 19.7% were orthopedics surgeries followed by 13.5% of mesh repair for abdominal hernia, 9.3% eversion of sac for Hydrocele, 8.7% appendectomy, 5.2% hysterectomy, 3% of pediatric herniotomy and others. Conclusion: GPs can be further trained to perform important common surgical procedures to improve access to surgical care for rural communities.